Compound 3d Attenuates Metabolic Dysfunction-Associated Steatohepatitis via Peroxisome Proliferator-Activated Receptor Pathway Activation and Inhibition of Inflammatory and Apoptotic Signaling - Shouqing Zhang; Jiajia Yu; Sule Bai; Shuhan Li; Quanyuan Qiu; Xiangshun Kong; Cen Xiang; Zhen Liu; Peng Yu; Yuou Teng (Metabolites)
Objectives: Metabolic dysfunction-associated steatohepatitis (MASH) lacks effective therapies. This study aimed to evaluate the therapeutic potential of compound 3d, a novel elafibranor derivative, focusing on its dual mechanisms of PPAR pathway activation and p38 MAPK signaling inhibition. Methods: Integrated in vitro and in vivo approaches were employed. In vitro, free fatty acid (FFA)-induced lipid accumulation in L02 hepatocytes and lipopolysaccharides (LPSs)-stimulated inflammatory responses in RAW264.7 macrophages were used to evaluate lipid metabolism and anti-inflammatory effects. In vivo, a high-fat diet (HFD)-induced MASH model in C57BL/6 mice assessed serum biochemical parameters (triglycerides (TGs), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), alanine aminotransferase (ALT), aspartate transaminase (AST), tumor necrosis factor-α (TNF-α), nitric oxide (NO), and interleukin-6 (IL-6)), liver histopathology (H&E, Oil Red O, Masson staining), and proteomic profiling. Gut microbiota composition was analyzed via 16S rRNA sequencing. Western blotting quantified PPAR isoforms (γ/δ), downstream targets (Acox1, EHHADH, Acaa1), and p38 MAPK pathway proteins (p-p38, caspase-8, Bcl-2). Results: In vitro, 3d significantly reduced lipid accumulation (reduction in TG, p < 0.01) and inflammation (decrease in ALT activity, p < 0.05) in hepatocytes, while suppressing LPSs-induced TNF-α (63% reduction), NO (51% decrease), and IL-6 (48% reduction) in macrophages (p < 0.01). In vivo, 3d (30 mg/kg) lowered serum TG (39% decrease), TC (32% reduction), LDL-C (45% decline), and TNF-α (57% reduction) in HFD-fed mice (p < 0.05 vs. model), normalized AST/ALT levels, and ameliorated hepatic steatosis, ballooning, and fibrosis. Proteomics demonstrated PPARγ/δ activation (2.3–3.1-fold upregulation of Acox1, EHHADH, Acaa1; p < 0.001) and p38 MAPK pathway inhibition (54% reduction in p-p38, 61% decrease in caspase-8; 1.8-fold increase in Bcl-2; p < 0.01). Gut microbiota analysis revealed enrichment of beneficial taxa (Lactobacillus: 2.7-fold increase; Bifidobacterium: 1.9-fold rise) and reduced pathogenic Proteobacteria (68% decrease, p < 0.05). Conclusions: Compound 3d alleviates MASH via PPAR-mediated lipid metabolism enhancement and p38 MAPK-driven inflammation/apoptosis suppression, with additional gut microbiota modulation. These findings highlight 3d as a multi-target therapeutic candidate for MASH.